Figure 3 from: Norarfan AF, Azreena Mokti SS, Taha H, Amin M, Ali M, Arai T (2021) DNA barcoding of a tropical anguillid eel, Anguilla bicolor (Actinopterygii: Anguilliformes), in Indo-Pacific region and notes on its population structure. Zoologia 38: 1-7. https://doi.org/10.3897/zoologia.38.e59332 - Norarfan, Ahmad Fathi; Azreena Mokti, Siti Shazwani; Taha, Hussein; Amin, Muhamad; Ali, Muhamad; Arai, Takaomi (Zenodo, 2021)
Figure 3 Haplotype network constructed with Anguilla bicolorCOI gene sequences. Each colour represents a sample site. The size of the circle is proportional to the number of samples that belong to each haplotype. White circle refers to median vector which is a hypothesized or missing haplotype. Each dash, which appears on the line that connects two haplotypes together, symbolizes one mutational step.